1984
DOI: 10.1121/1.391433
|View full text |Cite
|
Sign up to set email alerts
|

Minimum target size in radiation force measurements

Abstract: The necessary target size in acoustic radiation force measurements has not, up to now, been discussed in the literature in a systematic and quantitative manner. Making use of recent progress in the theoretical treatment of the radiation force of three-dimensional sound fields, this paper gives an assessment formula involving the target’s radius and distance from the source which is valid for the field of a baffled, circular, continuously vibrating piston source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In order to simplify the calculations, a lot of effort has been made [13]. Among them, Hasegawa [6] showed that the velocity potential at an observation point (r,θ ) in a focused field can be written as In expressions (7) and (8), j ( ) n x and (2) h ( ) n x are the spherical Bessel function and the spherical Hankel function of the second kind, P n (x) is the Legendre polynomial, and the time-dependent factor exp(jω t) is omitted. In spherical coordinates, the particle velocity can be read as…”
Section: Radiation Force On a Plane Absorbing Target In A Sphericallymentioning
confidence: 99%
See 3 more Smart Citations
“…In order to simplify the calculations, a lot of effort has been made [13]. Among them, Hasegawa [6] showed that the velocity potential at an observation point (r,θ ) in a focused field can be written as In expressions (7) and (8), j ( ) n x and (2) h ( ) n x are the spherical Bessel function and the spherical Hankel function of the second kind, P n (x) is the Legendre polynomial, and the time-dependent factor exp(jω t) is omitted. In spherical coordinates, the particle velocity can be read as…”
Section: Radiation Force On a Plane Absorbing Target In A Sphericallymentioning
confidence: 99%
“…Some corrections for finite size of the target should be made. Beissner [2] had suggested a minimum target size for plane piston sources. Therefore, when the acoustic power output from a transducer is determined through the radiation force measurements, it is crucial to establish a correct relationship between the radiation force and the corresponding acoustic power output for the radiated field of a practical transducer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 The technique recommended in IEC 61161 uses a radiation force balance (RFB). 6 An appropriately constructed target, properly aligned in a steady state under ultrasound field, is subjected to a radiation force given by [12][13][14] …”
Section: Introductionmentioning
confidence: 99%